CONCRETE QUALITY IN SEAWATER USING GGBFS AS A CEMENT SUBSTITUTE - Achmad, Ibanes Jean Gayatri; Amalia; Ulkhaq, Rafie Itharani (POLITEKNIK NEGERI JAKARTA, 2025)
Indonesia, as a maritime country, has many structures located in coastal and marine areas, which require the use of concrete with high resistance to aggressive environments. Seawater contains chloride and sulfate ions that can damage concrete structures, reduce strength, and accelerate the weathering process. On the other hand, the cement industry contributes significantly to global carbon emissions. One solution to enhance concrete durability while reducing carbon emissions is to use Ground Granulated Blast Furnace Slag (GGBFS) as a partial substitute for Portland cement. This study aims to analyze the quality of fresh concrete, including slump value, fresh concrete density, and initial setting time, as well as hardened concrete, including compressive strength, tensile strength, elastic modulus, and tensile stress, with concrete curing using seawater as the curing medium. The study was conducted by preparing concrete cylinder specimens with a water-cement ratio of 0.38. The specimens were prepared with four variations: 0%, 20%, 40%, and 60% of the cement weight. The study used Jalupang sand and Superplasticizer Nexplast N 6035 Admixture type F by PT. Nexco Indonesia. The results showed that the addition of GGBFS reduced the workability of fresh concrete but significantly increased compressive strength and elastic modulus at certain levels. The optimal composition was found at 40% GGBFS, which produced the best mechanical performance of concrete according to SNI standards. These findings indicate that GGBFS can be an effective environmentally friendly alternative material for improving concrete performance in seawater environments.